Reversing the established order: Should adrenal venous sampling precede cross‐sectional imaging in the evaluation of primary aldosteronism?. Issue 2 (17th July 2015) - Asmar, Melissa; Wachtel, Heather; Yan, Yan; Fraker, Douglas L.; Cohen, Debbie; Trerotola, Scott O.
<x xml:space="preserve">Abstract</x> Background Adrenal venous sampling (AVS) is the definitive evaluation for primary aldosteronism (PA). Pre‐AVS cross‐sectional imaging does not reduce the need for AVS. The goal of this study was to examine whether performing AVS prior to imaging could decrease the use of imaging in the evaluation of PA at a high volume, experienced center. Methods We performed a retrospective analysis of all AVS procedures (n = 337) done for PA from 2001–2013. Patients whose cross‐sectional imaging reports were unavailable (n = 90) or AVS was non‐diagnostic (n = 12) were excluded. AVS was performed using modified Mayo technique. Univariate analysis utilized the χ2 test and fisher's exact test. Results Of the 235 patients analyzed, 63% (n = 148) were male. The mean age was 55 ± 11 years. AVS was non‐lateralizing in 43% (n = 101); these patients might have avoided imaging with an AVS‐first approach. Imaging and AVS were concordant in 52% (n = 123). In patients ≤40yo (n = 23), 35% (n = 8) had no lateralization on AVS, and might have avoided imaging in an AVS‐first approach. Imaging and AVS were concordant in 52% (n = 12) of patients ≤40yo, versus 52% (n = 111) of patients >40yo (P = 0.987). Conclusion An AVS‐first, imaging‐second approach could have avoided CT/MRI in 43% of patients. At a high volume, experienced center, performing AVS first on patients with PA may reduce unnecessary cross‐sectional imaging studies. J. Surg. Oncol. 2015 111:144–148. © 2015 Wiley Periodicals, Inc.